TINGKAT PENGETAHUAN IBU HAMIL MENGENAI OMEGA-3 DAN OMEGA-6 TERHADAP KEHAMILAN DI KLINIK BERSALIN PERA SIMALINGKAR MEDAN TAHUN 2019 - Ermawaty Arisandi Siallagan (STIKes Santa Elisabeth Medan, 2019)
In the womb of a mother the fetus experiences amazing growth and development all the time. Many factors are needed to help the fetus grow optimally in the mother's uterus. Nutrient is one of the factors for fetal brain development. Although the fetal brain mass is only about 16% of the body, but compared to other organs, the brain requires the most energy, which is more than 70% for the process of growth and development. Omega-3 and Omega-6 substances more than 60% are needed as constituents of brain cells and neurons. From the study it was said that 55% of diagnoses of autism occur due to the lack of pregnant women consuming intakes containing omega-3 and omega-6, while genetic factors causing autism are only about 37%. Goals: This study aims to determine the extent to which pregnant women know the use of Omega-3 and Omega-6 for pregnancy in the Pera Simalingkar Maternity Clinic Medan in 2019. Method: This research is descriptive using primary data by distributing questionnaires to every pregnant woman who comes to visit to check her pregnancy to the Pera Simalingkar Maternity Clinic Medan with a total of 40 respondents. Result: From the results of the study respondents who were well-knowledgeed were 30%, quite knowledgeable were 55% and knowledgeable were less than 15%. Conculsion: From the data above, the knowledge of pregnant women about Omega-3 and Omega-6 regarding pregnancy is sufficient knowledge. It is recommended for health workers to further improve IEC regarding Omega-3 and Omega-6 for pregnancy to pregnant women.